2021
DOI: 10.1155/2021/6548554
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electrical Stimulation on Ocular Cells: A Means for Improving Ocular Tissue Engineering and Treatments of Eye Diseases

Abstract: Tissue engineering is biomedical engineering that uses suitable biochemical and physicochemical factors to assemble functional constructs that restore or improve damaged tissues. Recently, cell therapies as a subset of tissue engineering have been very promising in the treatment of ocular diseases. One of the most important biophysical factors to make this happen is noninvasive electrical stimulation (ES) to target ocular cells that may preserve vision in multiple retinal and optic nerve diseases. The science … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 78 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…Non-invasive electric stimulation (ES) is emerging as a therapeutic modality for eye and brain diseases ( Sanie-Jahromi et al, 2021 ). Clinical studies suggested that ES improves retinal function in eye diseases, such as retinitis pigmentosa ( Schatz et al, 2017 ), age-related macular degeneration (AMD) ( Shinoda et al, 2008 ), and central or branch retinal arterial occlusion ( Naycheva et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Non-invasive electric stimulation (ES) is emerging as a therapeutic modality for eye and brain diseases ( Sanie-Jahromi et al, 2021 ). Clinical studies suggested that ES improves retinal function in eye diseases, such as retinitis pigmentosa ( Schatz et al, 2017 ), age-related macular degeneration (AMD) ( Shinoda et al, 2008 ), and central or branch retinal arterial occlusion ( Naycheva et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Next, electrical stimulation will be created to evoke visual impressions. Weekly testing will be conducted for a period of 1 to 3 years (79).…”
Section: Intracortical Visual Prosthesis (Icvp) Projectmentioning
confidence: 99%
“…The parameters of electrical stimulation, namely waveform, intensity, frequency and duration can be varied according to purpose. Numerous studies demonstrate EF modulation to target the CNS both in vivo in animal models, clinical studies, or in vitro in cell cultures ( Sehic et al, 2016 ; Bertucci et al, 2019 ; Lancaster, 2019 ; Mobini et al, 2019 ; Krauss et al, 2021 ; Sanie-Jahromi et al, 2021 ). By increasing or decreasing EFs, studies have demonstrated the importance of endogenous EFs in normal development ( Levin, 2012 ; Smith et al, 2018 ; Iwasa et al, 2019 ; Sefton et al, 2020 ; Levin, 2021 ).…”
Section: Harnessing Electrical Fields In Vivo and ...mentioning
confidence: 99%
“…Electrical stimulation has been applied to the retina via several modes in vivo , either targeting the retina from the front or side of the eye, non-invasively, or alternatively directly contacting the retinal tissue (sub-retinal). Non-invasive EF modulation has been demonstrated to preserve vision in diseased retina in both animal models and clinical trials (Reviewed in Sehic et al, 2016 ; Sanie-Jahromi et al, 2021 ). As with deep-brain stimulation, further studies are required to elucidate full mechanisms of action.…”
Section: Enhancing Organoid Cultures With Bioelectricitymentioning
confidence: 99%
See 1 more Smart Citation